A symmetry reduction technique for higher order Painleve systems - Aratyn, H.; Gomes, J. F. [UNESP]; Zimerman, Abraham Hirsz [UNESP] (Elsevier B.V., 2012)
The symmetry reduction of higher order Painleve systems is formulated in terms of Dirac procedure. A set of canonical variables that admit Dirac reduction procedure is proposed for Hamiltonian structures governing the A(2M)((1)) and A(2M-1)((1)) Painleve systems for M = 2,3,.... (C) 2012 Elsevier B.V. All rights reserved.